2019
DOI: 10.3390/nu11051168
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Eating Behaviour Using Upper Limb Mounted Motion Sensors: A Systematic Review

Abstract: Wearable motion tracking sensors are now widely used to monitor physical activity, and have recently gained more attention in dietary monitoring research. The aim of this review is to synthesise research to date that utilises upper limb motion tracking sensors, either individually or in combination with other technologies (e.g., cameras, microphones), to objectively assess eating behaviour. Eleven electronic databases were searched in January 2019, and 653 distinct records were obtained. Including 10 studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 80 publications
(232 reference statements)
0
42
0
Order By: Relevance
“…Diet control is another way of weight management. Previous studies compared and confirmed the effectiveness of wearable devices in monitoring people's dietary behaviors (Heydarian, Adam, Burrows, Collins, & Rollo, 2019;Schiboni & Amft, 2018;Vu et al, 2017).…”
Section: Health Managementmentioning
confidence: 86%
“…Diet control is another way of weight management. Previous studies compared and confirmed the effectiveness of wearable devices in monitoring people's dietary behaviors (Heydarian, Adam, Burrows, Collins, & Rollo, 2019;Schiboni & Amft, 2018;Vu et al, 2017).…”
Section: Health Managementmentioning
confidence: 86%
“…Detecting and monitoring human eating behavior in the realworld is a growing field and offers exciting and novel opportunities for future public health research. Previous literature reviews on automatic eating detection methods have often placed a focus on sensor modalities and technologies in any research setting 28 , on specific sensor modalities, such as wearable video cameras 65 , or on specific sensor locations, such as the upper limb 29 . No review to date has focused specifically on studies that use wearable devices to automatically detect eating activity in naturalistic settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a range of wearable sensors for the purpose of automating eating detection have been proposed and studied. However, these studies have been primarily conducted in a combination of controlled lab and semi-controlled field settings 28,29 , and for good reason: these systems are challenging to develop, deploy, and evaluate. More recently, however, the research field has rapidly expanded the testing of these devices in the field.…”
Section: Introductionmentioning
confidence: 99%
“…A key aspect of smartwatches and activity monitors is that individuals wear and use them as part of their daily routine. Recent reviews concluded that smartwatches in particular represent an unobtrusive solution for both the tracking of eating behaviour 58 , and the delivery of targeted, context-sensitive recommendations promoting positive health outcomes 59 , such as Just-in-Time interventions 60 .…”
Section: When We Eatmentioning
confidence: 99%